Biohemijsko praćenje - vođeno kliničko upravljanje poboljšava inflamatorne i oksidativne profile stresa kod iznenadnog senzorineuralnog gubitka sluha: Biochemical Monitoring in SSNHL - Luo, Yafang; Wu, Jianin; Xie, Yeting (Journal of Medical Biochemistry, 2026)
Background: Sudden sensorineural hearing loss (SSNHL) is strongly linked to dysregulated inflammatory and oxidative stress pathways. However, the biochemical impact of applying these biomarkers to guide clinical management remains unclear. This study evaluated whether inflammation- and oxidative stress–based biochemical monitoring can optimize treatment responses and improve clinical outcomes in SSNHL. Methods: A total of 102 patients with SSNHL were randomly allocated to either a routine-management group or a biomarker-guided management group. Serial serum levels of C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), malondialdehyde (MDA), and superoxide dismutase (SOD) were quantified by ELISA before and after intervention. Hearing thresholds and quality-of-life indices were assessed concurrently. Results: Compared with routine care, biomarker-guided clinical management resulted in significantly greater reductions in CRP (12.33±1.08 vs. 18.76±1.62 mg/L), IL-6 (10.41±1.59 vs. 15.07±1.82 pg/mL), TNF-α (1.67±0.18 vs. 2.86±0.34 ng/mL), MDA (2.16±0.36 vs. 2.83±0.41 μmol/L), and SOD (1.82±0.15 vs. 2.40±0.22 KU/L) (all P < 0.001). These biochemical improvements were accompanied by larger decreases in air-conduction thresholds and better psychological, physical, general health, and social function scores. The incidence of treatment-related complications was also lower in the biomarker-guided group (5.88% vs. 21.57%). Conclusion: Biochemical monitoring of inflammation and oxidative stress pathways provides a structured and mechanism-oriented framework for managing SSNHL. Integrating serial CRP, IL-6, TNF-α, MDA, and SOD measurements into clinical decision-making can improve pathophysiological control, promote hearing recovery, and reduce adverse events. These results underscore the importance of biochemical biomarkers as actionable indicators for optimizing SSNHL management.